The AFNETA alley farming training manual. Volume 1. Core course in alley farming - Tripathi, B.R.; Psychas, P.J. (International Livestock Centre for Africa, 1992)
This training manual is a collaborative project of IITA, ILCA and ICRAF. The manual draws on articles, training materials, and illustrations prepared by scientists and support staff from the three institutions. It has been written with two readerships in mind. First it is intended for use in AFNETA's training courses and secondly, it is intended for any person interested in practicing or experimenting with alley farming. The topics covered in volume 1, i.e., core course in alley farming are, introduction to alley farming, multipurpose tree screening and evaluation, establishment and management of alley farming systems, the integration of livestock production in alley farming, on-farm research and socio-economic assessment of alley farming.